Analysis of Amoxicillin by Application of Hydrotropic Solubilization Phenomenon in Solid Dosage Form - MAHESHWARI, R.K.; DESWAL, S.; TIWARI, D.; ALI, N.; JAIN, S. (Asian Journal of Chemistry, 2010)
A novel, safe and sensitive method of spectrophotometric estimation in ultraviolet region has been developed using 5 M potassium acetate as hydrotropic solublizing agent for the quantitative determination of amoxicillin, a poorly water soluble antibiotic drug in tablet dosage form. Amoxicillin shows maximum absorbance at 274 nm. Beer's law was obeyed in the concentration range of 50-350 μg/mL.The hydrotropic agent and the additive used in formulation did not interfere in analysis. Proposed method is new, simple, accurate and reproducible. Statistical data proved the accuracy, reproducibility and the precision of the method.